Helicobacter pylori Biofilm Formation and Gene Expression on Abiotic Surfaces Using a Cyanobacterial Extract - Vega, Alba Edith (2012)
The effects of a cyanobacterial extract (CE) on Helicobacter pylori biofilm formation onto hydrophobic and hydrophilic abiotic surfaces and the expression of luxS, flaA, omp18, lpxD and ureA genes associated to biofilm were studied. NCTC11638 reference strain and HP796, a resistant clinical isolate, were grown in Mueller-Hinton broth supplemented with 5% fetal calf serum (FCS) or 1% CE. The ability to form biofilm, viability, morphological changes and gene expression of adhered H. pylori cells were determined. The strains were able to form biofilm on both surfaces with the nutritional supplements analyzed. H. pylori conserved a characteristic bacillary morphology and viability with CE. Cells attachment was higher with CE than FCS regardless of strains and surfaces. The most remarkable increase in gene expression was observed with the omp18 gene using the CE supplement, indicating the important participation of outer membrane proteins in biofilm establishment. The clinical isolate showed similar and even greater gene expression than the reference strain. The results obtained indicated that the nutrients provided by CE favored biofilm formation with retained pathogenicity that under certain conditions can occur in natural aquatic environments.